2010
DOI: 10.1021/ef101317f
|View full text |Cite
|
Sign up to set email alerts
|

H2SO4-Catalyzed Pyrolysis of Corncobs

Abstract: The acid-catalyzed pyrolysis of corncobs is investigated for the production of chemicals (in particular furfural) and bioproducts. Particles, preimpregnated with H2SO4 concentrations up to about 4% (dry sample mass basis) and predried at 343 K, are exposed in the form of a packed-bed at a heating temperature of 800 K. The gas release rate remains approximately constant, at a value about half with respect to the maximum detected for acid-free samples, for a large part of the process transients. Conversion times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 49 publications
6
39
1
Order By: Relevance
“…In comparison to R-bamboo, The absolute peak areas of furfurals obtained from R-bamboo and acid washed samples are presented in Fig 3B. It can be seen that the absolute peak areas of furfural from acid washed bamboo increased, whereas those of 2(3H)-furanone, 5-methyl-and 2,3-dihydrobenzofuran showed a contrary tendency. Previous study has demonstrated that furfural could be primarily formed by the dehydrations of pentosyl residues contained in hemicellulose and D-glucosyl residues presented in cellulose, and both of the two dehydration reactions were promoted by the residual hydrion from acids after acid washings (Branca et al, 2010). The absolute peak area of furfural from HF-bamboo was only slightly higher than that from R-bamboo probably due to its mild acidity.…”
Section: Relative Contents Of Different Groups Of Chemicalsmentioning
confidence: 91%
“…In comparison to R-bamboo, The absolute peak areas of furfurals obtained from R-bamboo and acid washed samples are presented in Fig 3B. It can be seen that the absolute peak areas of furfural from acid washed bamboo increased, whereas those of 2(3H)-furanone, 5-methyl-and 2,3-dihydrobenzofuran showed a contrary tendency. Previous study has demonstrated that furfural could be primarily formed by the dehydrations of pentosyl residues contained in hemicellulose and D-glucosyl residues presented in cellulose, and both of the two dehydration reactions were promoted by the residual hydrion from acids after acid washings (Branca et al, 2010). The absolute peak area of furfural from HF-bamboo was only slightly higher than that from R-bamboo probably due to its mild acidity.…”
Section: Relative Contents Of Different Groups Of Chemicalsmentioning
confidence: 91%
“…In particular, hexoses (galactoglucomannan), the major softwood hemicelluloses, give 5-HMF as one of the main degradation products, while pentoses (xylose, arabinose), constituting the main components of hardwood and hemicellulose residues, mainly degrade to FF. 33,35 Moreover, FF is also a secondary degradation product of other furanics, such as 5-MF and 5-HMF. 33,35 It is possible that the initial zone of constant yield observed in some cases is attributable to the increase in the percentage of cellulose in the sample following the disappearance of the hemicellulose during the pretreatment.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…H 3 PO 4 has been confirmed to be a promising catalyst for selective production of LGO [33,42]. In addition, H 2 SO 4 [32,43] and ionic liquid [31] have also been found to be capable for LGO production. Nevertheless, many problems will be encountered during the utilization of these liquid catalysts.…”
Section: Introductionmentioning
confidence: 99%